Knowledge, Attitude, Practice, and Adherence to Antiretroviral Therapy among People Living with HIV in Nepal - Sweta Shrestha; Subodh Chataut; Badri Kc; Khagendra Acharya; Sait Kumar Pradhan; Sunil Shrestha (AIDS Research and Treatment)
Introduction. Patient’s knowledge and attitude towards their treatment avert stereotypical misconceptions about the disease and its treatment, as well as aid in attaining optimal adherence. This study investigated the knowledge, attitude, practice, and adherence of antiretroviral therapy (ART) clients in Nepal. Method. A cross-sectional study was conducted among 165 ART clients visiting five ART sites in the far western region and the capital city of Nepal. The convenience sampling method was employed, and the data were collected through interviews with ART clients using a validated questionnaire. Binary logistic regression was used to identify associated factors. Result. Approximately 80.7% had adequate knowledge and 55% had a positive attitude towards ART. Stigmatization was associated with ARV by only 4.2%. Half of the participants (50.3%) revealed that they had surreptitiously stored their ART medication, diverging from the recommended storage guidelines. A significant proportion of respondents (33.3%) chose to repackage the medication as a strategy to prevent unintended disclosure of their HIV status. Many (59.3%) believed that ART does not prolong life. Nevertheless, they advocated the regular use of ART rather than taking it only when the health deteriorates (81.8%). The majority (97.6%) were found to be adherent to their ART. There was a significant association of age with a level of knowledge and attitude (p<0.05). A significant association was also found between knowledge and attitude towards ART (p<0.05). None of the variables had a significant association with adherence (p>0.05). Conclusion. Overall, adequate knowledge was demonstrated, whereas efforts are still needed to improve the attitude of ART clients towards ART. A need for counseling regarding the storage practices of ART is needed. A focus on ensuring the perfect translation of adequate knowledge and a positive attitude to the practice of ART clients is essential. Whether adequate ART knowledge and attitude scores will lead to near-perfect ART adherence needs further investigation.